The Experience of a Distance Learning Organization in a Private Higher Educational Institution in the Republic of Tatarastan (Russia): From Idea to Realization - Akhmetova, Daniya; Vorontsova, Liliya; Morozova, Ilona Gennadyevna (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
The article is devoted to the unique experience of distance learning development in the conditions of Russian reality. The model of distance learning in the Institute of Economics, Management and Law (Kazan city, Russia) is created on the basis of educational sphere diagnosis taking into account foreign and Russian experience. The specificity of the model is the permanent diagnosis of the components of the educational environment such as teacher qualifications, level of students’ actual knowledge, filling the educational process with information technologies, availability and quality of electronic resources, the correct choice of learning technologies, and policy in the field of the computerization of the professional education process.